SPECIAL EDUCATION, HEALTH AND INCLUSIVE PROCESSES: THE IMPORTANCE OF SCHOOL AND SOCIETY IN THE INCLUSION OF STUDENTS WITH DISABILITIES - Nunes Sapori, Aline (Revista Gênero e Interdisciplinaridade, 2023)
The article Special Education, Health and Inclusive Processes: The Importance of the School in the Inclusion of Students with Disabilities as a theme, aims to strengthen the attitudes of acceptance of individual differences and appreciation of human diversity, emphasizing the importance of belonging, coexistence, cooperation and the contribution that all people can make to build fairer community lives, healthier, more egalitarian and more satisfying. This is a bibliographic and qualitative study that aimed to survey bibliographic data presented in books and articles on the subject. In this sense, we searched for studies with the following keywords: Inclusion; School; Integration. The word inclusion implies the idea of segregation, since it is only possible to include someone who has already been excluded. Inclusion is supported by the inclusion/exclusion dialectic, with the struggle of minorities in the defense of their rights. The historic milestone of inclusion was in June 1994, with the Declaration of Salamanca, Spain, held by UNESCO at the World Conference on Special Educational Needs. Brazil is a signatory of international documents that define the unconditional insertion of people with disabilities in society, the so-called inclusion. However, it is not enough for Brazil to be a signatory to international treaties, to have fundamental guarantees of great impact, to have a specific status of Persons with Disabilities, with rights and duties, if we do not free ourselves from the mesmerizing positivist dogmas, seeking to ensure the rights already consecrated, in addition to announcing, through the insurgency, rights to those peoples still invisible and knowing that although we have solid constitutional and infraconstitutional matrices on the subject, We cannot settle for the great gulf between the legislative foundation, which is easy to enchant, and the practical reality, the daily life, the barriers and confrontations of those who experience the false inclusion and discrimination that exists today.